UPAYA PENINGKATAN MOTIVASI BELAJAR SISWA KELAS II MELALUI MEDIA PAPAN WAKTU DI SDN 01 MANISREJO - Deni Saputra; Prima Kurniawati, Rissa; Chasanah, Setyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to improve students' learning motivation in learning mathematics through time board media for second-grade students of SDN 01 Manisrejo. The type of research conducted is Classroom Action Research (CAR). The subjects of this study were 28 second-grade students of SDN 01 Manisrejo. The research design used was the Kemmis and MC Tagart spiral model consisting of planning, action, observation, and reflection stages. The data collection instruments used were observation and questionnaires. The data analysis techniques used were qualitative and quantitative data analysis. The results of the study showed that the application of time board media can improve mathematics learning motivation. This is evidenced by the increase in students' learning motivation in cycle I to cycle II. Cycle I obtained an average student learning motivation of 64.52% with a sufficient category. Furthermore, after implementing cycle II, the achievement of student learning motivation increased by 16.17% to 80.69% with a very good category.